PENGARUH LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PERILAKU KONFORMITAS DENGAN TEMAN SEBAYA PADA SISWA KELAS XI IPA SMA NEGERI 5 PEKANBARU TAHUN AJARAN 2014/2015 - Noli Noli '; Elni Yakub Elni Yakub; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aims of the present study 1) To know the description of peers conformity behavior before group guidance services are given,. 2) To know the implementation process of group guidance services forpeers conformity behavior, 3) To know the description of peers conformity bahavior after group guidance services are given. 4) To know the difference of peers conformity before and after group guidance services are given. 5) To determine the effect of group guidance to improve peers conformity behavior. The data collection that used is scale of peers conformity behavior . The subjects of the present study were administered to the students of science second grade students (XI IPA ) of SMAN 5 Pekanbaru totaling 30 students. The samples was used purposive sampling technique. The description before giving peers conformity behavior are lower category by 46.66% and very low by 53.33%. The description after giving peers conformity behavior are high category by 56.66% and 43.33% for medium category. Based on the calculation of coefficients correlation between x1 and x2 is 0.53 and the determinant coefficient = 0.28 it means that donations the group guidance services for peers conformity behavior by 28%. So, we know that Tcount greater than Ttable with significance level of 5% (25.16> 2.000) so that Ho refused and Ho accepted. It means that there is effect of group guidance services for improvement peers conformity behavior of science second grade students (XI IPA ) of SMAN 5 Pekanbaru academic year 2014/2015.Keywords: Group guidance services, Peers Conformity